Comparison of the registration process of the medicines control authority of Zimbabwe with Australia, Canada, Singapore, and Switzerland: benchmarking best practices. Issue 1 (2nd January 2022) - Sithole, Tariro; Salek, Sam; Mahlangu, Gugu; Walker, Stuart
ABSTRACT: Background: Benchmarking regulatory systems of low- and middle-income countries with mature systems provides an opportunity to identify gaps, enhance review quality, and reduce registration timelines, thereby improving patients' access to medicines. The aim of this study was to compare the medicines registration process of the Medicines Control Authority of Zimbabwe (MCAZ) with the regulatory processes in Australia, Canada, Singapore, and Switzerland. Methods: A questionnaire that standardizes the review process, allowing key milestones, activities and practices of the five regulatory authorities was completed by a senior member of the divisions responsible for issuing marketing authorizations. Results: The MCAZ has far fewer resources than the regulatory authorities in the comparator countries, but employs three review models, which is in line with international best practice. The MCAZ registration process is similar to the comparator countries in key milestones monitored, but differs in the target timelines for these milestones. The MCAZ is comparable to the comparator authorities in implementing the majority of good review practices, although it significantly lags behind in transparency and communication. Conclusion: This study identified the MCAZ strengths and opportunities for improvement, which if implemented, will enable the achievement of its vision to be a leading regulatory authority in Africa.